Case Report: Application of tumor-bearing bone inactivation and bilateral fibula grafting in joint-sparing surgery for osteosarcoma patient - Wang, Yapeng; Xu, Tian’en; Chen, Cong; Mai, Shuo; Yang, Kai (Frontiers in Surgery, 2025)
On August 28th, 2023, a 13-year-old male was diagnosed with conventional osteosarcoma of the proximal left tibia after a needle biopsy. Subsequently, the patient received two cycles of neoadjuvant chemotherapy and four cycles of postoperative chemotherapy. On December 27, 2023, the tumor resection was performed while preserving the knee joint, which involved inactivation of the tumor-bearing bone, autologous bilateral fibula grafting, and fixation of the grafted bone to the host bone using plate and screws. Follow-up after surgery included x-rays and CT scans. On February 28, 2024, two months after the surgery, new bone formation was noted at the site from which bone was harvested from the right fibula, the left knee joint had satisfactory range of motion in flexion (130°) and extension (0°). Additionally, partial healing of both the grafted bone and the host bone was observed. In the follow-up on September 23rd, 2024, nine months post-operation, the right fibula had reformed. Furthermore, the transplanted and host bones of the left tibia had healed securely. It was confirmed that there was no recurrence or metastasis of the tumor during the last follow-up by ECT. This case highlights the feasibility and effectiveness of using inactivating tumor-bearing bone and autologous bilateral fibular grafting to repair large bone defects after joint-sparing surgery for malignant tumors near the joints.